Mit Herkulesa we wszesnonowożytnych kronikach katalońskich. Komentarz i przekłady - Sasor, Rozalia (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
This article explores the presence of the Hercules myth in Iberian literature, focusing specifically on Catalan chronicles from the early modern period (Peter IV the Ceremonious, Tomic, Beuter and Carbonell). By tracing the chronological development of the legend, the study reveals the lines of borrowing and influence between initially separate Castilian and Catalan historiographical traditions, discusses the models and narratives that shaped the representation of Hercules in Catalan chronicles, and underscores the political motives behind the evolution of the myth. The article also provides translations with a commentary of the Catalan sources.